Tunable magnetic arrangement of iron oxide nanoparticles in situ synthesized on the solid substrate from diblock copolymer micelles - Yun, Sang-Hyun (Langmuir : the ACS journal of surfaces and colloids, 2005)
Hexagonal arrangement of iron oxide nanoparticles was fabricated by utilizing a single-layered film of diblock copolymer micelles. The synthesis was directly performed on the solid substrate by oxygen plasma with preserving the dimensional order of micelles so that separate procedures for synthesis and deposition of nanoparticles were not necessary. Since the oxygen plasma treatment also eliminated polymers, pure patterns of iron oxide nanoparticles were obtained. Moreover, easy control over the size of nanoparticles enabled us to selectively create a ferrimagnetic or a superparamagnetic pattern of iron oxide nanoparticles without altering the fabrication process